Export Competitiveness of Indonesian Cocoa Derivative Products in Main Destination Countries - Novi Rosanti; Firdasari; Soraya Alaini (Jurnal AGRISEP, 2025)
The purpose of this study is to examine the competitiveness of Indonesian cocoa derivative product exports, especially cocoa paste, cocoa butter, and cocoa powder, to the main destination countries: Malaysia, China, the Philippines, the United States, and India and to analyze the export trends of cocoa derivative products to make a forecast for the next 10 years. Data analysis includes the RCA (Revealed Comparative Advantage), ECI (Export Competitiveness Index) and ARIMA models. The results show that Indonesian cocoa paste has significant competitiveness in Malaysia, China, the Philippines, and the United States, but not in India because the RCA value is < 1. Indonesian cocoa butter and powder have a high competitive advantage in the main destination countries, indicated by the RCA value> 1. Indonesian cocoa paste, cocoa butter, and cocoa powder have been competitive since 2005 to 2022, indicated by the average ECI score > 1. In addition, the projection of Indonesia cocoa paste export prospects to major destination countries shows an increasing trend from 2023 to 2032, except for the Philippines which is expected to decline during that period, with an average of only 142.51 tons per year. The projection of the quantity of Indonesia cocoa butter exports to major destination countries shows an increasing pattern. The projection of the amount of Indonesia cocoa powder exports to Malaysia, China, the Philippines, and India is on an increasing trajectory; however, in the United States, it shows fluctuations with a downward trend with an average of 1,899,175 tons per year.